Remaja Millenial dan Media Sosial: Media Sosial Sebagai Media Informasi Pendidikan Bagi Remaja Millenial - Nur Ainiyah (Jurnal Pendidikan Islam Indonesia, 2018)
Social media is a communication medium that has synchronization in the delivered messages, A message delivered automatically to-share can’t be dammed. So it required caution in sharing information through social media. Millenial adolescence are human with all the curiosity of new things. The need for self-existence, increasing knowledge insight, other goals to make social media as a media of choice in communicating, shared information included to look for various information whom need today who grown and lived in the 21st century grow into millenial generation where social media and the internet became part of their daily life. So that social media is functioned by two things to them. The first is as a medium to build a social network through provided accounts, and android phone connected to the internet. The second is as a medium of educational information so that they can always access educational information through an account that becomes favorite teenagers.